Correlation between quality of cardiopulmonary resuscitation and self-efficacy measured during in-hospital cardiac arrest simulation; preliminary results - Gonzi, Gianluca; Sestigiani, Fiorella; D’errico, Antonella; Vezzani, Antonella; Bonfanti, Laura; Noto, Giancarlo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2015)
Background: The concept of self-assess it’s a central mechanism in human agency for behavior change and should translate to desirable practice patterns. There are no many studies that have investigated the relationship between the perception of the ability to perform cardiopulmonary resuscitation (CPR) and the quality of the same. The aim of this work is to investigate the relation between physiological and psychosocial variables in cardiac resuscitation in order to improve the involvement and motivation of professionals in training courses. Methods: During the year 2012, 322 medical staff of Ospedale-Universitario of Parma were trained to basic life support defibrillation (BLSD). Before started the course the partecipants were randomly selected among the staff working in the same department to create a team of two persons and involved in a simulation that reproduced the first five minutes that occurs for a cardiac arrest in a medical or surgical department in our hospital before the intervention of the hospital emergency team. Before and after simulation to each participant was asked to answer a self-efficacy questionnaire on a 10-point scale on the management of cardiac. During simulation were registered the activation time of the emergency response system, hands-on time, defibrillation time, number of compression and correct compression rate. Results: Activation time of the emergency response system was 70.52 ± 78.77 seconds. In 55 teams was not made the allert. The defibrillation time was 148.63 ± 58.43 seconds. In 44 teams the defibrillator were used within 120 seconds, in 36 (22.1%) it was not used. Hands-on time average was of 166.20 ± 62.9 seconds. The mean number of compression was 216.22 ± 115.57. The percentage of satisfactory compression was 9.97 ± 21.23 %. The level of self-efficacy was under the average for the 35.6%, while the 26.8% of the participants had a medium level of 5 and the 38.5% of the sample declared to feel an efficacy level included in 6-10. The sense of self efficacy after the simulation was constant in the 38.3% of the sample, while increased in the 30.5% and decreased in the 31.2%. We found no significant correlations between self-efficacy levels and specific results in scenario acting before simulation, instead, after the simulation the skills performances are much more correlated with self-efficacy. Conclusions: The medical staff reported an individual’s perception of good efficacy in the management of simulation of cardiac arrest, but it does not correspond to a high skills. An open question is if and how these psychosocial variables may play a role in improving the quality of CPR and if knowledge of the low capacity to manage a cardiac arrest can be translated into the need for the medical staff to be regularly engaged in BLSD retraining.